Raman Spectroscopic Analysis of Blood, Urine, Saliva and Tissue of Oral Potentially Malignant Disorders and Malignancy-A Diagnostic Study - PK Meenapriya; S Jaychandran; S Ganesan (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
Background: Oral cancers are mostly being preceded by oral potentially malignant disorders (OPMD). Early diagnosis of oral cancer or OPMDs speed up treatment and improve prognosis. Raman spectroscopy of blood, urine, saliva and tissue samples collected from OPMD and oral cancer patients were compared with similar samples from normal controls. Context and purpose: Raman spectroscopy is a noninvasive inelastic light scattering technique in which the wavelength of the incident laser light shifts depending on the vibrations of the molecules. The specific biochemical, structural and conformational changes occurring in tissues is reflected by their Raman spectra well before the clinical manifestations start. This helps in early diagnosis and speedy treatment planning. Results: Raman spectroscopy gave an accuracy of 78%, 90.5%, 93.1%, and 97.4% respectively for blood, urine, saliva and tissue samples in discriminating oral pre malignancy and malignancy from normal control. Conclusion: Results of the study validate that Raman spectroscopy has the potential to be a diagnostically useful tool for the in vitro detection of OPMDs and oral cancers at the molecular level. Brief Summary: Early diagnosis of OPMD and oral cancer by analyzing Raman spectroscopic changes improves the prognosis. Total sample size was 205. Spectra recorded on a confocal Micro Raman System (LABRAM HR 800) were statistically analyzed using the computer software SPSS/PC +19 under one of the multivariant technique analysis - Principal Component analysis followed with the Linear Discriminant Analysis (PC-LDA). The statistical analysis using PC-LDA combination of normal vs malignant vs premalignant group accuracy are shown.